2019
DOI: 10.1364/ol.44.005529
|View full text |Cite
|
Sign up to set email alerts
|

23  mJ high-power fiber CPA system using electro-optically controlled divided-pulse amplification

Abstract: The pulse-energy scaling technique electro-optically controlled divided-pulse amplification is implemented in a high-power ultrafast fiber laser system based on coherent beam combination. A fiber-integrated front end and a multi-pass cell based back end allow for a small footprint and a modular implementation. Bursts of 8 pulses are amplified parallel in up to 12 ytterbiumdoped large-pitch fiber amplifiers. Subsequent spatiotemporal coherent combination of the 96 total amplified pulse replicas to a single puls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…A thorough review of this technique can be found in Hanna et al, 2016;Klenke et al, 2018. The red circles in Figure 4 present recent Yb-fiber CPA systems incorporating DPA and CBC (Kienel et al, 2016;Klenke et al, 2013Klenke et al, , 2014Mueller et al, 2020;Muller et al, 2016Muller et al, , 2018Stark et al, 2019); femtosecond pulses with >100 mJ energy and >10 kW average power are expected in the near future.…”
Section: Linear Amplificationmentioning
confidence: 99%
“…A thorough review of this technique can be found in Hanna et al, 2016;Klenke et al, 2018. The red circles in Figure 4 present recent Yb-fiber CPA systems incorporating DPA and CBC (Kienel et al, 2016;Klenke et al, 2013Klenke et al, , 2014Mueller et al, 2020;Muller et al, 2016Muller et al, , 2018Stark et al, 2019); femtosecond pulses with >100 mJ energy and >10 kW average power are expected in the near future.…”
Section: Linear Amplificationmentioning
confidence: 99%
“…In contrast, kilowatt average power levels are routinely achieved with Yb-based diode-pumped ultrafast laser systems. Their architecture can be based on slab [23,24], fiber [25,26] or thin-disk geometries [27]. Pulse energy scaling has been particularly successful in thin-disk based regenerative amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of polarized beams can be done via polarization beam combiners or thin-film polarizers. Several representatives on power scaling of both CW and pulsed laser via polarization beam combiners have been led to the realization of tens of millijoules energy and kW level average powers [16,104,108,[170][171][172][173][174][175][176]. In 2010, Seise et al in a proof-of-principle experiment demonstrated the combination of two femtosecond fiber lasers with the combining efficiency of 97% [171].…”
mentioning
confidence: 99%
“…In an improvement in the PCFs technology, the large-pitch photonic-crystal fibers (LP-PCFs) concept was introduced for effective single-mode operation in PCF technology for power/energy scaling up [205]. Use of LP-PCFs have resulted in 22 GW peak power [16], 23 mJ single pulse [175], and kW level average power within CBC systems [174,176]. However, the major drawback of PCFs is high bending loss leading to the inconvenient large size of the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation